Accuracy and effectiveness of electronic pediatric early warning score (PEWS): A literature review - Dewi Natalia; Dian Ramawati (Holistik Jurnal Kesehatan, 2024)
Background: The Pediatric Early Warning Score (PEWS) is important in assessing the risk of worsening of the condition in hospitalized pediatric patients. PEWS can be done manually and electronically. Purpose: To determine the effectiveness of using electronic PEWS in inpatient pediatric patients. Method: Literature study using the PRISMA diagram approach. Search for articles using the PICO formula in the Pubmed, Science Direct, Google Scholar, Sage Journal and Scopus databases for 2017-2023 with the keywords "pediatric early warning score" OR "PEWS score", AND "electronic" AND "hospitalization" AND "accuracy" OR "effectiveness". Results: A total of four electronic PEWS were implemented with integration into electronic health records, two articles used mobile applications, and two articles used bedside electronic PEWS. PEWS can be applied in the emergency unit (IGD) and general inpatient wards to assess the level of emergency, predict deterioration and anticipate transfer to intensive care. Electronic PEWS is accurate in recording vital signs, measuring scores, improving treatment decision making, saving documentation time compared to manual PEWS. Conclusion: Electronic PEWS can be used to monitor hospitalized pediatric patients.   Keywords: Accuracy; Effectiveness; Electronic; Hospitalisation; Pediatric Early Warning Score.   Pendahuluan: Pediatric early warning score (PEWS) penting dalam memantau risiko kondisi memburuk pada pasien anak yang dirawat di rumah sakit. PEWS dapat dilakukan dengan manual dan elektronik. Tujuan: Untuk mengetahui efektifitas penggunaan PEWS elektronik pada pasien anak yang dirawat di rumah sakit. Metode: Studi literatur menggunakan pendekatan diagram PRISMA. Pencarian artikel dengan formula PICO pada database Pubmed, Science Direct, Google Scholar, Sage Jurnal dan Scopus dari tahun 2017-2023 dengan kata kunci “pediatric early warning score” OR “PEWS score”, AND “electronic” AND “hospitalization” AND “accuracy” OR “effectiveness”. Hasil: Sebanyak empat PEWS elektronik diterapkan dengan integrasi ke dalam electronic health record, dua artikel menggunakan aplikasi mobile, dan dua artikel menggunakan bedside PEWS elektronik. PEWS dapat diterapkan di ruang IGD maupun bangsal rawat inap umum untuk menilai tingkat kegawatan, memprediksi perburukan, dan mengantisipasi transfer ke perawatan intensif. PEWS elektronik akurat dalam perekaman tanda vital, ketepatan perhitungan skor, meningkatkan pengambilan keputusan perawatan, dan menghemat waktu dokumentasi dibanding PEWS manual. Simpulan: PEWS elektronik dapat digunakan untuk pemantauan pasien anak yang dirawat di rumah sakit.   Kata Kunci: Efektivitas; Elektronik; Ketepatan; Rawat Inap; Skor Peringatan Dini Pediatrik.